Delayed Laparoscopic Cholecystectomy After Percutaneous Transhepatic Gallbladder Drainage Versus Emergency Laparoscopic Cholecystectomy for Acute Cholecystitis: A Meta-Analysis - Cai, Shengbin; Ma, Xianhua (Turkish Journal of Gastroenterology, 2021)
Background: The purpose of this meta-analysis is to appraise the efficacy and safety of delayed laparoscopic cholecystectomy afterpercutaneous transhepatic gallbladder drainage (PTGBD) versus emergency laparoscopic cholecystectomy (ELC) for acute cholecystitis.Methods: The kinds of literature were searched by Web of Science, PubMed, OVID, Cochrane Library, and EMBASE between the year2000 and 2019. RevMan 5.3 was used for meta-analysis.Results: Seventeen studies with 2135 participants were included in our study. Compared with the ELC group, delayed laparoscopic cholecystectomy after percutaneous transhepatic gallbladder drainage group (PTGBD group) had a significant better effect in intraoperative bleeding (P = .002), conversion rate to open surgery (P = .02), postoperative complications (P ＜ .00001), bile leakage (P = .01), bileduct injury (P = .02), and wound infection (P = .02). There was no significant difference between the two groups in operative time (P= 32),postoperative hospital stay (P = .30), and intraperitoneal hemorrhage (P = .39). PTGBD group had a significantly longer overall hospitalstay than the ELC group (P ＜ .00001).Conclusion: Compared with the ELC group, the PTGBD group has several advantages, including bile duct injury, intraoperative bleeding,bile leakage, conversion rate to open surgery, postoperative complications, and wound infection. The only drawback in the PTGBD groupis to lengthen the total hospital stay